AFGHANISTAN: ITS ROLE AND PLACE IN THE INTERNATIONAL SECURITY SYSTEM - AKMALOV, Shaislam (CENTRAL ASIA AND THE CAUCASUS, 2009)
For three decades now the country has been struggling for survival amid a never-ending armed conflict that makes a concerted foreign policy course impossible. This is fraught with a loss of statehood and is responsible for Afghanistan’s role and place in the international relations system. The military-political crisis in Afghanistan is echoing across Central and Southern Asia and is spreading its negative impact even further across the world. Farkhad Tolipov, a political analyst from Uzbekistan, has rightly noted that strategic “friction”in Afghanistan is closely connected with the geopolitical reversal occurring in the Central Asian states.e has written that “friction” makes it much harder to pursue strategic and tactical aims and that, if they are achieved at all, the cost will be enormous. The Afghan crisis is largely responsible for the geopolitical instability in Central Asia, which affects its security.1 The foreign policy activities of the Central Asian states and the world community as a whole have to take the Afghan factor into account. President of Uzbekistan Islam Karimov has written:The deepness and acuteness of the Afghan crisis and its obvious impact on the geopolitical proc-esses at the regional and global levels allow us to describe this tragedy as the largest and the most dangerous regional conflict of our time. The military-political crisis in Afghanistan is inevitably affecting regional stability in Central Asia and Uzbekistan’s national security, in particular, in the most negative way.”2